Growth, Agar Yield and Water Quality Variables Affecting Mass Propagation of Tissue Cultured Seaweed Gracilaria verrucosa in Pond - Sri Redjeki Hesti Mulyaningrum; Hidayat Suryanto Suwoyo (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2018)
Mass propagation of tissue culture produced seaweed seedling was conducted in the pond. The present study aims to evaluate the growth of tissue culture produced seaweed seedling of Gracilaria verrucosa, its agar yield and related water quality variables during propagation in pond. The seedling propagation was conducted in pond using long line method for 9 cycles (30 days per cycle). The daily growth rate was calculated by weighing 30% of the total amount of seaweed at ropes line every 15 days. Agar yield was analyzed every 30 days in hot water extraction method. Water quality monitoring was conducted every 15 days. The data of daily growth rate and agar yield were analyzed descriptively. A simple linear regression analysis was conducted in order to analyze the relationship between growth and agar yield as well relationship between water quality variables, growth and agar yield. The result showed that the average daily growth rate of nine cycles was 3.38±1.49%. The highest agar yield was yielded from cycle II (27.84±1.60%) and the lowest was in cycle I (10.30%±2.15). There is no relationship between daily growth rate and agar yield (R2=0.055). Daily growth rate was mostly influenced by phosphate (P<0.05), nitrate (P<0.05), salinity (P<0.05) and light penetration (P<0.05). Meanwhile, agar yield was mostly influenced by temperature (P<0.05) and light penetration (P<0.05). Present study promising for seaweed G. verrucosa mass cultivation of tissue culture product which is a feasible alternative method to supply seaweed seedlings in seaweed farming development.  Keywords: growth, agar yield, G. verrucosa, tissue culture, water quality